2021
DOI: 10.1001/jamanetworkopen.2021.27573
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dyslipidemia and Availability of Lipid-Lowering Medications Among Primary Health Care Settings in China

Abstract: IMPORTANCE Dyslipidemia, the prevalence of which historically has been low in China, is emerging as the second leading yet often unaddressed factor associated with the risk of cardiovascular diseases. However, recent national data on the prevalence, treatment, and control of dyslipidemia are lacking.OBJECTIVE To assess the prevalence, treatment, and control of dyslipidemia in community residents and the availability of lipid-lowering medications in primary care institutions in China. DESIGN, SETTING, AND PARTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 37 publications
6
61
1
Order By: Relevance
“…Second, benefiting from the centralized medicine procurement policy in China, the annual cost of treatment per patient with moderate-intensity statins has reduced from $300 to $50 ( 18 ), making the treatment more affordable. The next step should be to ensure that statins is more widely available, given its unavailability in nearly half of the primary care institutions, especially rural village clinics ( 29 ). Third, there are still around 11 million Chinese people at high or very-high ASCVD risk requiring ezetimibe and/or PCSK9 inhibitors; however, the prices of the two drugs in China (i.e., annual $380 for ezetimibe, and $5,182 for evolucumab 140 mg per patient) are even higher than those in some high-income countries ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, benefiting from the centralized medicine procurement policy in China, the annual cost of treatment per patient with moderate-intensity statins has reduced from $300 to $50 ( 18 ), making the treatment more affordable. The next step should be to ensure that statins is more widely available, given its unavailability in nearly half of the primary care institutions, especially rural village clinics ( 29 ). Third, there are still around 11 million Chinese people at high or very-high ASCVD risk requiring ezetimibe and/or PCSK9 inhibitors; however, the prices of the two drugs in China (i.e., annual $380 for ezetimibe, and $5,182 for evolucumab 140 mg per patient) are even higher than those in some high-income countries ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] It is noteworthy that high triglycerides and low HDL-c are the main types of dyslipidemia in the Chinese population, in contrast to the predominance of high TC and high LDL-c in the United States and Europe. [38] This feature suggests that management of triglycerides in the Chinese population may yield greater benefit. The role of triglycerides in the development of cardiovascular disease has received increasing attention in recent years, yet the protective effect of triglycerides control has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The nationwide study InterASIA in 2000–2001 provided the first glimpse into the prevalence of dyslipidemia in China, which found that 53.6% of adults aged 35–74 years had dyslipidemia, and in regard to its components, 9.0%, 5.1%, and 19.2% had high total cholesterol, high low-density lipoprotein cholesterol (LDL-C), and low high-density lipoprotein cholesterol (HDL-C), respectively [ 7 , 41 ]. Studies in 2014–2019 revealed a consistently high prevalence of dyslipidemia in China, ranging from 33.8 to 43% among adults of middle or senior ages; presentations with high triglycerides (16.9–22.4%) and low HDL-C (15.6–19.9%) were more common compared with high total cholesterol (7.1%–11.3%) and high LDL-C (4.0–8.1%) [ 42 44 ]. Among adults aged ≥ 18 years, the prevalence of high total cholesterol, high triglycerides, high LDL-C, and low HDL-C was reported to be 6.9%, 13.8%, 8.1%, and 20.4% in 2013–2014, respectively [ 45 ].…”
Section: Methodsmentioning
confidence: 99%